Rat flea disease vector control: literature review - tami, dwitami (Research of Environmental Science and Engineering, 2020)
In the 14th century, the Black Death killed 50 million people in Europe, thus reducing 60 percent of Europe's population. This event is caused by the yersinia pestis bacteria found in rat fleas/fleas that live near humans. There are more than 2000 species of fleas, one of which is the species Xenopsylla coreopsis. This study aims to provide information on the vector of rat flea disease and control. This study used a literature study method with a focus on the rat flea disease vector. The cause of this vector-borne disease is a dirty lifestyle. Poor sanitation and water channels are one of the causes of disease caused by fleas vectors. Clogged drains and sewers full of trash are home to the rats who are infested with fleas. But in fact, we as humans live side by side with other living things so that a healthy lifestyle does not guarantee that we are entirely safe from vector-borne diseases. The creation of this paper is one way to increase public awareness of rat flea vector-borne diseases and appropriate control to avoid this rat flea disease.